Portrayal of Kashmir Issue in the Editorial Cartoons of English Dailies: A comparative study of Indian and Pakistani newspapers - khan, Maham Zahid; Maira Qaddos,; Muhammad Suleman, (Journal of Peace, Development and Communication, 2021)
Kashmir issue has been the bone of contention between India and Pakistan since their independence. However, abrogation of article 370 on Aug 05, 2019, in Indian Occupied Kashmir by the Indian government to revoke its’ special status has escalated the conflict to an extreme level. This paper is an attempt to examine the portrayal of the Kashmir issue in the editorial cartoons of English dailies of India and Pakistan published in August 2019 (just after the abrogation of the article 370) in the light of Framing theory and Barthes’s model of connotation and denotation. The main objective of this research is to examine the signs, symbols, and metaphors used by Pakistani and Indian cartoonists to highlight the Kashmir issue. The study concludes both Pakistani and Indian newspapers frame the Kashmir issue in their way representing their perception, newspaper's policy, and ideology. Cartoons published in Indian newspapers depict Pakistan as a confused and baffled state whereas Pakistani newspapers highlight the barbarianism of the Indian army in the Indian Occupied Kashmir.